2021
DOI: 10.21203/rs.3.rs-778091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and Evaluation of Effective Strategies in a Dynamic Visual Task Using Eye Gaze Dynamics

Abstract: Simulation-based training utilising visual displays are common in many defence and civil domains. The performance of individuals in these tasks depends on their ability to employ effective visual strategies. Quantifying the performance of the trainees is vitally important when assessing training effectiveness and developing future training requirements. The approach, attitudes and processes of an individual’s learning varies from one to another. In this light, some visual strategies may be better suited to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…For example, in surveillance tasks, operators monitoring several screens can be supported by systems that track gaze behavior and automatically notify the operator to adjust their scanning pattern [4]. In a simulated task, Veerabhadrappa, et al [5] found that participants achieved higher performance on a simulated UAV refuelling task when they maintained a longer gaze on the relevant region of interest compared to less relevant regions. Further, in training scenarios, gazebased measures can identify operator attention allocation and quantify progress of novice operators [6].…”
Section: A On Gaze-based Behavioral Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in surveillance tasks, operators monitoring several screens can be supported by systems that track gaze behavior and automatically notify the operator to adjust their scanning pattern [4]. In a simulated task, Veerabhadrappa, et al [5] found that participants achieved higher performance on a simulated UAV refuelling task when they maintained a longer gaze on the relevant region of interest compared to less relevant regions. Further, in training scenarios, gazebased measures can identify operator attention allocation and quantify progress of novice operators [6].…”
Section: A On Gaze-based Behavioral Studiesmentioning
confidence: 99%
“…We can see the ROI in green in the Figure 3. We use functions made by Dinu C. Gherman to define the ROI by giving points in an image 5 . Fig.…”
Section: Gaze To Objectsmentioning
confidence: 99%